2003
DOI: 10.2143/ac.58.6.2005321
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcysteine, coronary procedure and prevention of contrast-induced worsening of renal function

Abstract: Our data do not support the systematic use of acetylcysteine before a coronary procedure in patients with normal renal function or mild to moderate chronic renal failure, to prevent contrast-induced nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 0 publications
0
23
0
4
Order By: Relevance
“…Another reason is the controversial data obtained from orally administered NAC [102] . As in the studies with oral NAC, the results with IV NAC have also been inconsistent [102][103][104][105][106][107][108][109][110] . The clinical trials comparing IV NAC and control groups for RCIN after angiography are shown in Table 5.…”
Section: Nac Treatmentmentioning
confidence: 94%
“…Another reason is the controversial data obtained from orally administered NAC [102] . As in the studies with oral NAC, the results with IV NAC have also been inconsistent [102][103][104][105][106][107][108][109][110] . The clinical trials comparing IV NAC and control groups for RCIN after angiography are shown in Table 5.…”
Section: Nac Treatmentmentioning
confidence: 94%
“…In all but two studies [33,36], NAC was administered orally. In the majority of studies, 2 doses of NAC (600 mg each) were administered on the day before, and on the day of intravenous administration of contrast media.…”
Section: Nacmentioning
confidence: 99%
“…Cumulative dosages varied from 1500 mg to 4800 mg. In all but two studies [28,31], NAC was administered orally.…”
Section: Clinical Trials On Prevention Of Contrast-induced Nephropathymentioning
confidence: 99%
“…Although five trials found a significant protective effect of NAC compared with standard treatment [22,25,27,30,32], eight found no beneficial effect of administration of NAC [13,23,24,26,28,29,31,35]. Possible explanations for these contrasting results are differences in applied hydration regimens, in the patient populations studied and in the volumes of contrast media administered, and variations in the timing and dosing of NAC.…”
Section: Clinical Trials On Prevention Of Contrast-induced Nephropathymentioning
confidence: 99%